2022
DOI: 10.1097/iae.0000000000003609
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Primary and Secondary Forms of Multiple Evanescent White Dot Syndrome

Abstract: The aim of this study was to compare primary versus secondary forms of multiple evanescent white dot syndrome (MEWDS) at T0 (baseline) and T1 (1-4 months after the onset of symptoms).Methods: A total of 101 eyes in 100 patients were included in a multicentric retrospective study.Results: Secondary MEWDS was defined as MEWDS associated with underlying chorioretinal inflammatory pathologies, mainly multifocal choroiditis and punctuate inner choroidopathy. Patients with secondary MEWDS were older (P = 0.011). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
7
2
Order By: Relevance
“…Some of their findings were consistent with ours, such as gender composition, BCVA and multimodal inflammation scores at baseline, time from onset to presentation, etc. 19 Yet the authors also found that the patients with primary MEWDS had older age, better BCVA, and lower multimodal inflammation scores during follow-up, which is inconsistent with this work. However, they included a mixture of many different triggers of secondary MEWDS, including MFC/PIC, CNV, ocular toxoplasmosis, birdshot chorioretinopathy, etc.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…Some of their findings were consistent with ours, such as gender composition, BCVA and multimodal inflammation scores at baseline, time from onset to presentation, etc. 19 Yet the authors also found that the patients with primary MEWDS had older age, better BCVA, and lower multimodal inflammation scores during follow-up, which is inconsistent with this work. However, they included a mixture of many different triggers of secondary MEWDS, including MFC/PIC, CNV, ocular toxoplasmosis, birdshot chorioretinopathy, etc.…”
Section: Discussioncontrasting
confidence: 79%
“…It is well-known that mild signs of intraocular inflammation are typical characteristics of both primary MEWDS and most inflammatory pathologies underlying secondary MEWDS, including MFC/ PIC. 1,19 Based on our observation, we believe that signs of intraocular inflammation have a limited role in helping identify primary MEWDS and MEWDS secondary to MFC/PIC.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations